Воспользуемся формулами:
1)
2)
3)
Решение.
Доказано.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Воспользуемся формулами:
1)![sin\alpha+sin \beta=2* sin\frac{\alpha+\beta}{2}*cos\frac{\alpha-\beta}{2} sin\alpha+sin \beta=2* sin\frac{\alpha+\beta}{2}*cos\frac{\alpha-\beta}{2}](https://tex.z-dn.net/?f=sin%5Calpha%2Bsin%20%5Cbeta%3D2%2A%20sin%5Cfrac%7B%5Calpha%2B%5Cbeta%7D%7B2%7D%2Acos%5Cfrac%7B%5Calpha-%5Cbeta%7D%7B2%7D)
2)![cos\alpha+cos \beta=2*cos\frac{\alpha+\beta}{2}*cos\frac{\alpha-\beta}{2} cos\alpha+cos \beta=2*cos\frac{\alpha+\beta}{2}*cos\frac{\alpha-\beta}{2}](https://tex.z-dn.net/?f=cos%5Calpha%2Bcos%20%5Cbeta%3D2%2Acos%5Cfrac%7B%5Calpha%2B%5Cbeta%7D%7B2%7D%2Acos%5Cfrac%7B%5Calpha-%5Cbeta%7D%7B2%7D)
3)![tg\alpha =\frac{sin\alpha}{cos\alpha} tg\alpha =\frac{sin\alpha}{cos\alpha}](https://tex.z-dn.net/?f=tg%5Calpha%20%3D%5Cfrac%7Bsin%5Calpha%7D%7Bcos%5Calpha%7D)
Решение.
Доказано.